2013
DOI: 10.1371/journal.ppat.1003222
|View full text |Cite
|
Sign up to set email alerts
|

OncomiR Addiction Is Generated by a miR-155 Feedback Loop in Theileria-Transformed Leukocytes

Abstract: The intracellular parasite Theileria is the only eukaryote known to transform its mammalian host cells. We investigated the host mechanisms involved in parasite-induced transformation phenotypes. Tumour progression is a multistep process, yet ‘oncogene addiction’ implies that cancer cell growth and survival can be impaired by inactivating a single gene, offering a rationale for targeted molecular therapies. Furthermore, feedback loops often act as key regulatory hubs in tumorigenesis. We searched for microRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 50 publications
(99 reference statements)
1
79
0
2
Order By: Relevance
“…We compared host miRNA expression levels in cells infected with Toxoplasma , Theileria or Cryptosporidium using our dataset and previously published datasets and this revealed that these apicomplexan parasites modulate the expression of a restricted panel of miRNAs in a specific manner, most likely in order to suit their respective biology. This can be illustrated by miR-155, a microRNA implicated in immune response (Lindsay, 2008) that was strongly induced by both Toxoplasma (Figures S1B) and Theileria (Marsolier J et al, 2013) while being unaffected by Crytosporidium infection (Zhou et al, 2009). …”
Section: Resultsmentioning
confidence: 97%
“…We compared host miRNA expression levels in cells infected with Toxoplasma , Theileria or Cryptosporidium using our dataset and previously published datasets and this revealed that these apicomplexan parasites modulate the expression of a restricted panel of miRNAs in a specific manner, most likely in order to suit their respective biology. This can be illustrated by miR-155, a microRNA implicated in immune response (Lindsay, 2008) that was strongly induced by both Toxoplasma (Figures S1B) and Theileria (Marsolier J et al, 2013) while being unaffected by Crytosporidium infection (Zhou et al, 2009). …”
Section: Resultsmentioning
confidence: 97%
“…This results in deregulation of the p53 checkpoint pathway and is critical for parasite pathogenesis. Theileria infection induces expression of the miR-155 oncomiR, which targets DET1, a component of the ubiquitin ligase complex containing DNA damage-binding protein 1 (DDB1) (Marsolier et al, 2013). These recent studies provide evidence for links between parasite-encoded proteins and host signaling pathways that regulate apoptosis and damage signaling.…”
Section: Pathogen Oncoproteins and Genotoxins And Their Intersection mentioning
confidence: 99%
“…In fact, the use of Theileria-transformed bovine cells to study these phenotypes has already begun, with Theileria-transformed bovine cells being used as a xenograft model in mice [98]. Using standard cancer biology assays, in vitro systems have been developed as well [19]. The fact that no genomic instability has been reported in infected cells may indicate an absence of the confounding effects of the 99.9% bystander mutations that are found in most cancer cell lines [99].…”
Section: Discussionmentioning
confidence: 99%
“…Pattern-recognition receptors can also activate NF-kB to induce in vivo antimicrobial programs that are crucial for innate and adaptive immunity [16], and many pathogens have the ability to suppress NF-kB signaling [17,18]. The IkB kinase (IKK) complex activates NF-kB, and Theileria schizonts have been shown to constitutively activate the IKK complex on their cell surface, possibly by trans-autophosphorylation [19]. Consequently, investigations into the mechanisms by which Theileria parasites manage to evade the immunostimulatory effects of NF-kB signaling provide an opportunity to discover novel therapeutics against Theileria infection.…”
Section: Mechanisms Of Theileria-induced Proliferative Signalingmentioning
confidence: 99%
See 1 more Smart Citation